Factors influence online donation during COVID-19 pandemic - Muhamad Nafik Hadi Ryandono; Aditya Kusuma; Anny Maryani; Ida Wijayanti (Universitas Negeri Surabaya, 2022)
The Covid-19 pandemic has caused changes in human behaviour, including payment transaction methods from cash to non-cash. In addition, the National Non-Cash Program (GNTT) by Bank Indonesia (BI) also supports this new behaviour. This non-cash payment also occurs in donation payments, including zakat, infaq, alms and other Islamic social funds. This research analyses the factors influencing user behaviour (UB) towards the online donation from cash to non-cash. This study uses quantitative research within Partial Least Square – Structural Equation Modeling (PLS-SEM) tools. The data of this study is compiled by questionnaire on 124 respondents in East Java who made online donations during the Covid-19 pandemic (March 2020 – 2021). This research uses a technology adaptation model that is the UTAUT (Unified Theory of Acceptance and Use of Technology) model using the facilitating conditions (FC), performance expectancy (PE), effort expectancy (EE) and social influence (SI) variables. The results of this study indicate that (a) FC has a positive and significant effect on PE and SI, (b) PE and SI have a positive and significant effect on EE, and (3) PE and SI have a positive and significant effect on UB. Meanwhile, ease of donating online (Effort Expectancy) does not provide influence user behaviour of online donations. In addition, recommendations are also given to online donation organisations to improve collaboration, credibility and use of promotion media.